Larangan Penggunaan Ponsel Saat Mengemudi Kendaraan Bermotor - Abd Kudus Zaini; Muchammad Zaenal Muttaqin; Rizdqi Akbar Ramadhan; Tessa Shasrini; Yulia Herawaty; Ditta Fisdian (Prisani Cendekia, 2022)
Traffic accidents caused by the use of cell phones while driving are increasing, resulting in fatalities, serious injuries and minor injuries as well as significant material losses. The effect of cell phone use on driving performance can distract drivers and lead to a ban on the use of cell phones while driving a motor vehicle. The purpose of this study was to determine the characteristics of cell phone use among motorized vehicle drivers in the city of Pekanbaru. The activity method is to communicate with cellphones while driving. This community service activity uses methods in the form of mentoring through lectures, demonstrations, microteaching and questions and answers. The stages in the implementation of the activities are: 1. Lectures are used to convey general knowledge about the use of mobile phones for traffic safety. 2. Demonstrations are used to provide hands-on skills regarding the handling process related to problems related to traffic safety. 3. Questions and answers are used to complete things that have not been accommodated by the two methods above. 4. Simulation of discussion activities and traffic laws for traffic safety 5. Interaction between teacher and student teams in implementing mobile phones.